Julius Caesar - Firth, Rachel (London Usborne Publishing Ltd, 2007)
Presents the life and accomplishments of the Roman general and statesman whose brilliant military leadership helped make Rome the center of a vast empire
Include Color Illustration
Keywords: Rome (Empire) -- Caesar, Julius -- Generals